4th International Conference on Telecommunications in Modern Satellite, Cable and Broadcasting Services. TELSIKS'99 (Cat. No.99
DOI: 10.1109/telsks.1999.806241
|View full text |Cite
|
Sign up to set email alerts
|

MESFET noise modeling based on noise wave temperatures

Abstract: A simple procedure for extraction the intrinsic noise wave temperatures in the wave representations of microwave transistors is presented in this paper. A set of equation describing the noise parameters as the function of three equivalent noise temperatures is implemented within the circuit simulator Libra. After that, the wave noise model is defined as new user-defined element of program Libra library. Good agreement between modeled and measured noise parameters is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…However, it is shown that it is the most useful to use the noise wave temperatures as the noise wave model parameters [2,12]. Therefore, the correlation matrix C T can be expressed by the noise wave temperatures -two real temperatures, T a and T b , and one complex correlation temperature, T c , as:…”
Section: Fig 2 Two Port Noisy Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is shown that it is the most useful to use the noise wave temperatures as the noise wave model parameters [2,12]. Therefore, the correlation matrix C T can be expressed by the noise wave temperatures -two real temperatures, T a and T b , and one complex correlation temperature, T c , as:…”
Section: Fig 2 Two Port Noisy Networkmentioning
confidence: 99%
“…Most of the proposed transistor noise models represent the noise generated in a component using equivalent voltage and/or current sources [3,[5][6]. However, at microwave frequencies, a wave representation of noise looks attractive since it allows the use of scattering matrices for the noise computations, leading to advantages in Computer-Aided Design (CAD) of microwave networks [2,[7][8][9][10][11][12][13][14][15][16][17][18]. The power of the wave representation of noise lies in its ability to treat the network noise in terms of incident and reflected waves, which is compatible with the scattering matrix description of microwave networks.…”
Section: Introductionmentioning
confidence: 99%
“…It is very convenient to use the noise wave temperatures as empirical noise model parameters, [12]. In that way, the correlation matrix C T can be expressed by…”
Section: Fig 2 2t Representation Of a Linear Noisy Two-portmentioning
confidence: 99%
“…Therefore, during the last few decades an extensive work has been carried out in the field of signal / noise modelling of microwave transistors. There is a number of different models, starting from accurate physical models which require knowledge about the numerous technological parameters [1,2], through the widely used empirical models, mostly based on equivalent circuit representation of a transistor [3][4][5][6][7][8][9][10][11][12][13][14][15], to the models based on the application of the artificial neural networks, based either on the black box modelling approach [16,17] or on a combination with the empirical models [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation